Bacterial spot of tomato and pepper: diverse Xanthomonas species with a wide variety of virulence factors posing a worldwide challenge. (29th April 2015) - Potnis, Neha; Timilsina, Sujan; Strayer, Amanda; Shantharaj, Deepak; Barak, Jeri D.; Paret, Mathews L.; Vallad, Gary E.; Jones, Jeffrey B.
Summary Taxonomic status Bacteria; Phylum Proteobacteria; Class Gammaproteobacteria; Order Xanthomonadales; Family Xanthomonadaceae; Genus Xanthomonas; Species Xanthomonas euvesicatoria, Xanthomonas vesicatoria, Xanthomonas perforans and Xanthomonas gardneri. Microbiological properties Gram‐negative, rod‐shaped bacterium, aerobic, motile, single polar flagellum. Host range Causes bacterial spot disease on plants belonging to the Solanaceae family, primarily tomato (Solanum lycopersicum), pepper (Capsicum annuum) and chilli peppers (Capsicum frutescens). Disease symptoms Necrotic lesions on all above‐ground plant parts. Distribution Worldwide distribution of X. euvesicatoria and X. vesicatoria on tomato and pepper; X. perforans and X. gardneri increasingly being isolated from the USA, Canada, South America, Africa and Europe. A wide diversity within the bacterial spot disease complex, with an ability to cause disease at different temperatures, makes this pathogen group a worldwide threat to tomato and pepper production. Recent advances in genome analyses have revealed the evolution of the pathogen with a plethora of novel virulence factors. Current management strategies rely on the use of various chemical control strategies and sanitary measures to minimize pathogen spread through contaminated seed. Chemical control strategies have been a challenge because of resistance by the pathogen. Breeding programmes have been successful in developing commercial lines with hypersensitive and quantitative resistance. However, durability of resistance has been elusive. Recently, a transgenic approach has resulted in the development of tomato genotypes with significant levels of resistance and improved yield that hold promise. In this article, we discuss the current taxonomic status, distribution of the four species, knowledge of virulence factors, detection methods and strategies for disease control with possible directions for future research.